2020
DOI: 10.1111/sji.12924
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term in vitro persistence of magnetic properties after magnetic bead‐based cell separation of T cells

Abstract: Magnetic‐activated cell sorting (MACS) using magnetic nanoparticles coated with specific antibodies is commonly used in immunology research. For in vitro isolation purposes, it is important to know to what extent the magnetic properties remain present in the isolated cell populations and whether it has consequences for sequential isolations. We hypothesized that only upon cell division, cells will lose their magnetic properties via dilution of the particles in/on their daughter cells. We analysed residual magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Superparamagnetic particles-antibody coupling technique combined with magnetic isolation is shown to be capable of minimizing the effects introduced by fluorescent antibodies occupancy thanks to its effective separation with only unsaturated concentration of bead-antibody conjugates (Grutzkau and Radbruch, 2010; Plouffe et al, 2015). However, concerns arising from the use of nanosized magnetic beads include internalization of magnetic beads and preservation of magnetic properties for an extended period in cells that are subjected to limited proliferation, which calls for caution when repetitive positive isolation steps after in vitro culture are required (Laghmouchi et al, 2020; Teeman et al, 2019). More recently, Miltenyi Biotec has introduced the REAlease Fluorochrome Technology that relies on engineered antibody fragments with low epitope binding affinities which allows stained antibodies to be released.…”
Section: Introductionmentioning
confidence: 99%
“…Superparamagnetic particles-antibody coupling technique combined with magnetic isolation is shown to be capable of minimizing the effects introduced by fluorescent antibodies occupancy thanks to its effective separation with only unsaturated concentration of bead-antibody conjugates (Grutzkau and Radbruch, 2010; Plouffe et al, 2015). However, concerns arising from the use of nanosized magnetic beads include internalization of magnetic beads and preservation of magnetic properties for an extended period in cells that are subjected to limited proliferation, which calls for caution when repetitive positive isolation steps after in vitro culture are required (Laghmouchi et al, 2020; Teeman et al, 2019). More recently, Miltenyi Biotec has introduced the REAlease Fluorochrome Technology that relies on engineered antibody fragments with low epitope binding affinities which allows stained antibodies to be released.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of pericytes also inhibited the proliferation of other ingredients when the culture conditions changed, which was confirmed in the present study by flow cytometry. Fluorescence‐activated cell sorting, differential centrifugation and MACS are common methods for cell separation [ 21 ]. Fluorescence‐activated cell sorting is time‐consuming and easily contaminated, and the survival rate of cultured cells is low.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic particles have to be biocompatible, as any toxic effects might compromise the cell isolation as well as the cell quality and the therapeutic efficiency of the cell-based treatment [26]. The MAGicBeads consist of biodegradable material, such as agarose and iron oxide, and these materials are known to be not harmful to cells [27]. To ensure the MAGicBeads biocompatibility for stem cells, a toxicity test was performed with hMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, possible multiple attachment points for the cells can provide a more robust system for a potential scale-up. Additionally, studies have shown that the cells can retain the magnetic properties of the IMS up to 2 weeks after initial isolation [27] providing a potential safety risk. In the same study, it was also shown that these small magnetic beads can be taken up by the cells and have been found on the cell surface and in the intra-cellular spaces [27].…”
Section: Discussionmentioning
confidence: 99%